Women who contributed to past research in multiple sclerosis. (October 2019) - McCombe, Pamela A
Background: The history of multiple sclerosis (MS) is dominated by the discoveries of famous men. However, women would like to feel part of the story and to know that women have contributed to MS research. Objective: To identify women who contributed to the history of discovery in MS. Method: This was a personal survey from my knowledge of previous work. Results: There were no women participants in the early stages of MS research. However, since 1950 there are many women who have contributed to MS research. In the 20th century, there were famous women who contributed to the scientific fields that form the basis of MS research. In the 21st century, more women participate in MS research but studies suggest that they are under-represented in positions of prominence. Conclusion: Women have been part of the effort to understand MS, but are not well recognized.